Kemiripan Sekuen Mouse Mammary Tumor Virus dengan Human Mammary Tumor Virus pada Kanker Payudara - Shintia Christina; Puspita Eka Wuyung (Jurnal Kedokteran Meditek, 2011)
Abstrackhuman breast cancer incidence varied around the world, where the incidence in Asia is lower than western. Different types if mice in both parts of the world suggestive associated with the incidence of human breast cancer, in which M.domesticus the main carrier of virus more widely available in western. Mouse Mammary Tumor Virus (MMTV) is a type B retrovirus that causes breast cancer in mice. MMTV has a genome consisting of longterminal Repeat (LTR), Pol, Gag, Pro, and Env. MMTV has the ability to tumorigenesis by insertion mutagenesis and may affect genes that are close to the insertion. Transmission of this virus occurs through two channels, namely endogenous and exogenous. Endogenous pathways through the germline, while the exogenous pathway the milk. Several studies have shown the existence of sequence similarity in Env and MMTV LTR by human breast cancer, so that suspected a link between MMTV in human breast cancer. The presence of MMTV in the rate of progression of disease was also found in line, where the higher the degree of malignancy of a tumor also increased the number of MMTV sequences. However, until now we do not know how the MMTV can infect humans, so its role as a cause of human breast cancer is uncertain.Key words : MMTV, breast cancer